Ideology of Translating Cultural Terms in Novel "Laut Bercerita" into "The Sea Speaks His Name" - Santika, Pelsi; Sofyan, Dedi; Yunita, Wisma (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objective of this study was to find out the ideology frequently applied in translating cultural terms of the novel Laut Bercerita and The Sea Speaks His Name. This study used qualitative research. The data source of this study was the Indonesian novel Laut Bercerita by Leila S. Chudori and the English translation entitled The Sea Speaks His Name by John H. McGlynn. To collect the data, the researcher identified the words or phrases in the novel Laut Bercerita and The Sea Speaks His Name. The results of this study showed that domestication, which had 167 data (74.2%), was more dominant than foreignization, with 58 data (25.8%) in the category of ideology in translating cultural terms. Domestication covered five categories of cultural terms, such as ecology, material culture, social culture, organization, customs, activities, procedures, and concepts, gestures and habits, while foreignization covered four categories of cultural terms, such as ecology, material culture, social culture, and organization, customs, activities, procedures, and concepts. In conclusion, the translator applied domestication in which the translator changed the cultural terms that were suitable for the culture in the target language in order to produce an acceptable and understandable translation for the target audience.